Study of cytogenetic abnormalities in G-CSF stimulated peripheral blood cells and non-stimulated bone marrow cells of patients with myelofibrosis - Lozynskyy, R.Y.; Lozynska, M.R.; Hontar, Y.V.; Huleyuk, N.L.; Maslyak, Z.V.; Novak, V.L. (Experimental Oncology, 2016)
The aim of the study was to improve cytogenetic diagnostics and monitoring of myelofibrosis and to reveal the spectrum of cytogenetic abnormalities in patients from Ukraine. Materials and Methods: A total of 42 patients (23 females and 19 males) with myelofibrosis was studied using different cytogenetic methods. Granulocyte colony-stimulating factor (G-CSF) was added by the new method during cultivation of peripheral blood (PB) cells from 31 patients for specific stimulation of mitotic divisions. Two patients underwent examination by fluorescent in situ hybridization method. Results: In cell cultures of PB stimulated in vitro with G-CSF and in non-stimulated bone marrow chromosome abnormalities were found in 19 (45.2%) of all the patients. The spectrum of cytogenetic abnormalities of bone marrow and PB was the same in all of the patients. Aspiration of bone marrow was unsuccessful due to significant fibrosis in 10 (29.4%) of 34 patients. The study by fluorescent in situ hybridization method confirmed cytogenetic abnormalities revealed by G-method and discovered additional possibly normal subclone. Conclusions: Cytogenetic study of PB using in vitro G-CSF as a specific stimulant of mitosis instead of phytohemagglutinin revealed significant variety of chromosomal abnormalities in Ukrainian patients with myelofibrosis. This method could be a less invasive alternative to cytogenetic examination of bone marrow in the subgroup of patients with considerable fibrosis and consecutive changes. The usage of fluorescent in situ hybridization method supplemented karyotyping by G-banding method.